KEBIJAKAN PEMERINTAH INDONESIA DALAM MENANGGULANGI ILLEGAL FISHING PADA TAHUN 2014-2015 - T. Muhammad Almuzzamil; Khairul Anwar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Measures to eradicate IUU fishing in the future will continue to be improved and improved, given that in essence the granting of rights in the form of fishing permits, followed by the obligation to carry out responsible fishing activities, in order to preserve the resources of fish and its environment , To support food security, minimize economic losses from stolen fish resources, and protect fishing businesses by domestic fishing fleets.The purpose of this study is to first explain the policies of the Indonesian government in handling Ilegal Fishing capture that occurred in Indonesian territorial waters. Secondly, explaining the bureaucracy structure of marine and fishery ministries in handling Ilegal Fishing catches in Indonesian waters. Third, explaining the potential of Resources Humans in guarding the waters of Indonesia. In this research, writer use descriptive research type with qualitative analysis method. The location of this research is Indonesia. The choice of Indonesia to be the location of research because often the case of Ilegal Fishing. This research uses state building theory and bureaucratic theory. Technique of collecting data in this research that is literature conducted by collecting secondary data in this matter represented by information from literature-literature relevant to problem studied, with consideration of data collecting in this research qualitatively based on bibliography research covering book , Relevant journals, newspapers and the internet. Qualitative research method is an option in this study because the author wants to explore the study more deeply by looking at the phenomenon and reality that exist in this study.Based on the results of analysis of this study shows that: The various ways that the Indonesian government to tackle the problem of illegal fishing, such as strengthening the bureaucratic structure through the ministry of marine and fisheries by forming teams or parts that specifically handle illegal fishing, strengthening legislation through revision To regulate legal fishing permit and legal strengthening of criminal acts illegal fishing actors also improve the quality of human resources by conducting various activities to increase knowledge and insight society in the water area.Keywords: policy, tackling, ilegal fishing, ministry of marine and fisheries